A method for preparing an ohmic contact test structure

By adding an oxide layer to the preparation of the ohmic contact test structure and peeling off the oxide layer and metal layer by using wet etching technology, the metal pattern edges are easily burrs and photoresist contamination in the preparation of the ohmic contact test structure in the prior art are solved. The machine problem improves the accuracy and pass rate of the product.

CN117594428BActive Publication Date: 2025-02-14XIAN WEIGUANG TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410071980.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-02-14
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

In the prior art, the preparation method of ohmic contact test structures is prone to burrs on the edges of metal patterns, resulting in poor pattern deformation and peeling effects, and photoresist is prone to carbonization and contamination of the machine at high temperatures, reducing the product pass rate.

Method used

The oxide layer is formed on the surface of the substrate layer and the photoresist is coated on the oxide layer. The cover area and the non-cover area are formed by exposure and development. The exposed oxide layer in the non-cover area is etched and removed, and the cover area is removed. The photoresist inside forms several spaced oxide layers, and then forms a metal layer on the surface of the oxide layer and the epitaxial layer. The oxide layer and the metal layer are peeled off by wet etching to obtain an ohmic contact test structure.

Benefits of technology

By adding an oxide layer as a medium, the photoresist is avoided from contacting the metal layer directly, the machine is contaminated, and the accuracy of the ohmic contact test structure and the product pass rate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117594428B_ABST
    Figure CN117594428B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of semiconductor technology, and in particular to a method for preparing an ohmic contact test structure, comprising the following steps: providing a substrate layer; forming an oxide layer on the surface of the substrate layer; coating photoresist on the oxide layer, exposing and developing to obtain a cover glue area and a non-cover glue area; etching to remove the exposed oxide layer in the non-cover glue area; removing the photoresist in the cover glue area to obtain a plurality of spaced oxide layers; forming a metal layer on the surface of the plurality of spaced oxide layers and the exposed epitaxial layer; and stripping the plurality of spaced oxide layers and the metal layer on the surface thereof by wet etching to obtain an ohmic contact test structure. That is, the scheme of the present invention can obtain an accurate ohmic contact test structure, thereby improving the qualified rate of products produced online.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of semiconductor technology and more specifically to a method for preparing an ohmic contact test structure. Background Art

[0002] As a representative of the third generation wide bandgap semiconductor materials, SiC has excellent properties that Si materials do not have. Its high breakdown field strength, high electron mobility and high thermal conductivity are gradually replacing Si-based power devices and are used in the high-end market. However, it is precisely because of the unique physical and chemical properties of SiC that the preparation of SiC power devices also requires some special process technologies.

[0003] Ohmic contact is one of the key factors affecting the application of silicon carbide devices in extreme environments such as high temperature and easy oxidation. Its purpose is to achieve the smallest possible voltage drop when the electrode is under the application of forward voltage, so as to ensure the performance of the device. If the ohmic contact is degraded or fails, it will inevitably affect the on-resistance of the device. In severe cases, it will affect the performance of the device and even cause the device to fail. Therefore, it is particularly necessary to design an ohmic contact test structure with good thermal stability and oxidation resistance.

[0004] In the prior art, the preparation methods of ohmic contact test junctions are generally divided into direct etching method and photoresist stripping method. Among them, the photoresist stripping method is usually used in laboratories, and its disadvantages are as follows:

[0005] First, when the photoresist is stripped by vibration, burrs are easily generated on the edge of the metal pattern, which may even cause serious deformation of the pattern and poor stripping effect.

[0006] Second, since the method first sputters or evaporates on the wafer to form a metal layer, and then removes the photoresist, and the photoresist is an organic substance that will carbonize at high temperatures, it is easy to contaminate the machine during the sputtering or evaporation process of contacting the metal, thereby reducing the qualified rate of online products. For example, the patent document with the authorization announcement number CN107546112B and the invention name "SiC Ohmic Contact Structure and Its Manufacturing Method" discloses a method for manufacturing a SiC Ohmic Contact Structure, wherein in step (b), a mask is used to photolithograph the surface of the substrate shown to form a CTLM pattern, and a DC magnetron sputtering process is used to sequentially deposit metal layers on the substrate surface; the above scheme obviously has the problem of easily contaminating the machine, thereby reducing the qualified rate of products.

[0007] Therefore, it is particularly important to optimize the preparation process of the ohmic contact test structure to obtain a precise ohmic contact test structure and thereby improve the qualified rate of products produced online. Summary of the invention

[0008] To solve one or more of the above technical problems, the present invention provides a method for preparing an ohmic contact test structure, which can obtain an accurate ohmic contact test structure, thereby improving the qualified rate of online produced products. To this end, the present invention provides a solution in the following aspect.

[0009] The present invention provides a method for preparing an ohmic contact test structure, comprising the following steps:

[0010] providing a substrate layer;

[0011] forming an oxide layer on the surface of the substrate layer;

[0012] Coating photoresist on the oxide layer, and obtaining a photoresist cover area and a non-photoresist cover area through exposure and development;

[0013] Etching to remove the exposed oxide layer in the non-capping glue area;

[0014] Removing the photoresist in the cover glue area to obtain a plurality of spaced oxide layers;

[0015] forming a metal layer on the surfaces of the oxide layers and the exposed epitaxial layer;

[0016] Wet etching is used to peel off several spaced oxide layers and metal layers on their surfaces to obtain an ohmic contact test structure; wherein the wet etching uses a BOE solution or a HF solution.

[0017] Optionally, a dry etching process is used to etch away the exposed oxide layer in the non-capping glue area; the parameters of the dry etching process include: etching gas, time, power and pressure.

[0018] Optionally, before forming the oxide layer, the method further includes forming an epitaxial layer on the surface of the substrate layer.

[0019] Optionally, the method further includes testing the electrical properties of the ohmic contact tests prepared in the same batch, and querying the abnormalities of the process parameters or equipment in the preparation method based on the electrical properties to ensure the pass rate of the ohmic contact test structure.

[0020] Optionally, the steps of ensuring the pass rate of the ohmic contact test structure are:

[0021] Testing the electrical properties of the ohmic contact test structures of the same batch; the electrical properties include resistance values ​​measured at different temperatures;

[0022] Based on the electrical properties of the ohmic contact test structures of the same batch, density clustering is performed on the ohmic contact test structures of the same batch to achieve binary classification and determine the abnormal category;

[0023] Obtain the current process parameters of each ohmic contact test structure in the abnormal category, calculate the consistency between the current process parameters and the normal process parameters, if the consistency is greater than the set threshold, the abnormal process parameters may be normal, then the staff is reminded to repair the equipment; otherwise, the staff needs to adjust the process parameters to re-prepare the ohmic contact test structure.

[0024] Optionally, the density clustering adopts a DBSCAN clustering algorithm.

[0025] Optionally, the consistency is obtained by comparing the difference between each process parameter and a normal process parameter, and calculating the ratio of the number of parameters whose difference is less than a set value to the total number of process parameters.

[0026] Optionally, the chemical solution for wet etching is an acid solution; the acid solution includes a BOE solution or a HF solution.

[0027] The beneficial effects of the present invention are:

[0028] The scheme of the present invention increases an oxide layer and uses the oxide layer as a medium to transfer the test pattern from the photoresist to the metal layer through the oxide layer, and after the metal layer is formed, the oxide layer is stripped, thereby ensuring that the machine is not contaminated and improving the qualified rate of the ohmic contact test structures of the same batch.

[0029] Furthermore, the solution of the present invention verifies the qualification rate of the prepared ohmic contact test structure by testing the electrical properties of the ohmic contact test structure, and inquires about abnormalities in process parameters or equipment, so that a qualified ohmic contact test structure can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] By reading the following detailed description with reference to the accompanying drawings, the above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0031] Figure 1 A schematic diagram of a transmission line model test pattern is schematically shown;

[0032] Figure 2 A schematic diagram of a circular transmission line model test pattern is schematically shown;

[0033] Figure 3 A flow chart schematically shows a method for preparing an ohmic contact test structure in this embodiment;

[0034] Figure 4A schematic cross-sectional view of a first intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0035] Figure 5 A schematic cross-sectional view of a second intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0036] Figure 6 A schematic cross-sectional view of a third intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0037] Figure 7 A schematic cross-sectional view of a fourth intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0038] Figure 8 A schematic cross-sectional view of a fifth intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0039] Fig. 9 A schematic cross-sectional view of a sixth intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0040] Fig.10 A schematic cross-sectional view of a seventh intermediate product structure corresponding to a method for preparing an ohmic contact test structure in this embodiment is shown;

[0041] Fig.11 A schematic cross-sectional view of a final product structure of a method for preparing an ohmic contact test structure in this embodiment is shown;

[0042] Description of the drawings: 1. Substrate layer; 2. Epitaxial layer; 3. Oxide layer; 4. Photoresist; 5. Metal layer. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0044] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0045] Figure 1 A schematic diagram of a transmission line model test pattern is schematically shown. Figure 2A schematic diagram of a circular transmission line model test pattern is shown schematically.

[0046] In the prior art, commonly used methods for performing ohmic contact tests on ohmic contact test structures include transmission line measurement model method (TLM) and circular electrode transmission line measurement model method (CTLM). Both methods require the preparation of corresponding test structures (test patterns) on wafers.

[0047] For TLM, the test pattern is shown in Figure 1 , requiring the formation of multiple unequally spaced metal patterns (wherein the metal patterns are rectangular) on the wafer substrate; for CTLM, the test pattern is shown in Figure 2 , it is required to form multiple metal patterns (the metal patterns are metal rings) on the wafer substrate; the size and spacing of each metal pattern corresponding to each measurement model method are as close to the design value as possible; therefore, how to accurately form the test pattern on the wafer substrate layer is a current concern.

[0048] Based on the above problems, the present invention provides a method for preparing an ohmic contact test structure, namely, before metal sputtering or evaporation, the photoresist is first removed, and after metal sputtering or evaporation, several spaced oxide layers and the metal layer on their surface are removed to obtain an ohmic contact test structure; thereby, accurate test patterns can be obtained and the product qualification rate can be improved.

[0049] Figure 3 A flow chart of a method for preparing an ohmic contact test structure in this embodiment is schematically shown.

[0050] Specifically, Figure 3 As shown, a method for preparing an ohmic contact test structure in this embodiment includes the following steps:

[0051] In step S1, a substrate layer is provided. Figure 4 As shown, the first intermediate product structure in this embodiment includes a substrate layer 1; the substrate layer 1 is a silicon carbide (SiC) substrate; of course, the material of the substrate layer 1 can also be at least one of the following materials: Si, Ge, SiGe, SiGeC, InAs, GaAs, InP, InGaAs or other III / V compound semiconductors, etc. The substrate layer 1 can have a P-type conductivity type or an N-type conductivity type.

[0052] At the same time, the substrate layer 1 is also cleaned, that is, the RCA cleaning method is adopted, wherein the RCA cleaning includes three different solutions - SC1, hydrofluoric acid and SC2; the SC1 solution contains ammonium hydroxide, hydrogen peroxide and water, which can usually effectively remove particles and metals on the substrate layer 1; the SC2 solution contains hydrochloric acid, hydrogen peroxide and water, which can usually effectively remove alkali metal ions and metal hydroxides that are insoluble in ammonia water; hydrofluoric acid (HF) strips any natural oxide from the surface.

[0053] In step S2, an oxide layer is formed on the surface of the substrate layer.

[0054] Specifically, in this embodiment, an oxide layer can be directly deposited on the substrate layer 1 , but it is required that the substrate layer 1 must be heavily doped, that is, the substrate layer 1 is a heavily doped substrate.

[0055] In another embodiment, an epitaxial layer may be formed on the substrate layer 1 in this embodiment, and an oxide layer may be formed on the epitaxial layer. The substrate layer 1 may be a heavily doped substrate or a non-heavy doped substrate.

[0056] It should be noted that when making a CTLM pattern, it can be made directly on a heavily doped substrate; while when making a TLM pattern, it requires an epitaxial layer on the substrate.

[0057] The heavily doped substrate layer or epitaxial layer mentioned above is for improving the performance of the ohmic contact test structure obtained subsequently.

[0058] In this embodiment, taking the formation of an oxide layer on the epitaxial layer as an example, Figure 5 As shown, the second intermediate product structure in this embodiment includes a substrate layer 1 and an epitaxial layer 2; that is, an epitaxial layer 2 is formed on the substrate layer 1, and the epitaxial layer 2 can have the same material as the substrate layer 1, and the lattice of the epitaxial layer 2 is matched with the substrate layer 1, thereby reducing the migration of defects in the substrate layer 1 to the epitaxial layer 2. Of course, epitaxial implantation can also be performed to obtain a heavily doped epitaxial layer 2. Since epitaxial implantation is a conventional process, it will not be described in detail here.

[0059] In one embodiment, an epitaxial growth process may be used to form the epitaxial layer 2. Specifically, the epitaxial growth process includes low pressure chemical vapor deposition (LPCVD), plasma enhanced chemical vapor deposition (PECVD), ultra-high vacuum chemical vapor deposition (UHVCVD), rapid thermal chemical vapor deposition (RTCVD) and molecular beam epitaxy (MBE).

[0060] like Figure 6As shown, the third intermediate product structure in this embodiment is a product structure in which an oxide layer 3 is formed on the basis of the second intermediate product structure, that is, the oxide layer 3 is deposited on the epitaxial layer 2, wherein the material of the oxide layer 3 is silicon dioxide with a thickness of 10000~20000Å; the oxide layer 3 can specifically be produced by PETEOS (Plasma Enhanced Tetraethyl Orthosilicate) process or LPTEOS (Low-Pressure Tetraethyl Orthosilicate) process; of course, other existing oxidation processes can also be used to generate it, such as furnace tube oxidation, rapid thermal annealing oxidation (RTO), in-situ steam oxidation (ISSG), etc.

[0061] In step S3, photoresist is coated on the oxide layer, and a photoresist cover area and a photoresist non-cover area are obtained through exposure and development.

[0062] For example, Figure 7 As shown, the fourth intermediate product structure in this embodiment is a product structure coated with photoresist 4 on the basis of the third intermediate product structure, that is, photoresist 4 is coated on the oxide layer 3, and then the photoresist covering area and the non-photoresist covering area are obtained after exposure and development.

[0063] In step S4, the exposed oxide layer in the non-capping glue area is removed by etching.

[0064] For example, Figure 8 As shown, the fifth intermediate product structure in this embodiment is a product structure after removing the exposed oxide layer 3 in the non-capping glue area based on the fourth intermediate product structure; that is, the exposed oxide layer 3 in the non-capping glue area is removed by a dry etching process, and the oxide layer 3 corresponding to the capping glue area is retained; wherein the dry etching process can be reactive ion etching (RIE), ion beam etching or plasma etching, etc. wherein the parameters of the dry etching process include: etching gas, time, power and pressure.

[0065] In step S5, the photoresist in the cover glue area is removed to obtain a plurality of spaced oxide layers.

[0066] For example, Fig. 9 As shown, the sixth intermediate product structure in this embodiment is a product structure after the photoresist 4 on the fifth intermediate product structure is removed, and the product structure has a plurality of spaced oxide layers 3. Among them, the photoresist 4 in the cover glue area on the fifth intermediate product structure composed of the oxide layer 3 with the photoresist 4, the epitaxial layer 2 and the substrate layer 1 is removed by plasma bombardment and SPM cleaning methods.

[0067] In step S6, a metal layer is formed on the surfaces of the oxide layers and the exposed epitaxial layer. Fig.10 As shown, the seventh intermediate product structure in this embodiment is a product structure in which a metal layer 5 is formed on the basis of the sixth intermediate product structure; specifically, the metal layer 5 is formed on the oxide layer 3 and the epitaxial layer 2, which is achieved by a physical deposition process, that is, by thermal evaporation or sputtering, the metal is converted from a solid and liquid state to a gas state in a vacuum, and condensed on the surface of the oxide layer 3 and the epitaxial layer 2 to form the metal layer 5.

[0068] The metal layer 5 can be one of Ni, Ti, and Al. Specifically, the metal layer 5 in this embodiment is Ni. It should be noted that when metal sputtering or evaporation is performed, the photoresist has been removed from the intermediate product to avoid machine contamination.

[0069] In step S7, wet etching is used to peel off several spaced oxide layers and the metal layer on the surface thereof, and high temperature annealing is performed to finally obtain an ohmic contact test structure.

[0070] like Fig.11 As shown, the final product structure in this embodiment is the product structure after the oxide layer 3 and the surface metal layer 5 on the seventh intermediate product structure are stripped off; specifically, in this embodiment, a wet etching process is used for etching, wherein the chemical solution for wet etching is an acid solution; the acid solution includes a BOE solution or an HF solution. Taking the BOE solution as an example, it is a mixture of hydrofluoric acid (49%) and water or ammonium fluoride and water.

[0071] At the same time, general acid has a high selectivity for metal when stripping the oxide layer 3 and hardly corrodes the metal. Therefore, only the metal on SiO2 will be stripped along with SiO2, while the metal not in contact with SiO2 is hardly corroded, thus ensuring the accuracy of the graphic size.

[0072] The high temperature annealing mentioned above may be furnace annealing, RTP (Rapid Thermal Processing) rapid annealing, laser annealing, etc.

[0073] In this embodiment, in step S7, high temperature annealing may be performed first, and then the oxide layer 3 may be stripped. This is because the oxide layer 3 hardly reacts with the metal Ni at high temperature, and thus annealing may be performed first and then stripping may be performed.

[0074] It should be noted that the terms "first intermediate product structure", "second intermediate product structure", "third intermediate product structure", "fourth intermediate product structure", "fifth intermediate product structure", "sixth intermediate product structure", "seventh intermediate product structure" and "final product structure" mentioned above are intended to characterize the structures corresponding to the process steps of the preparation method of an ohmic contact test structure in this embodiment; of course, it can also be expressed in other terms.

[0075] At the same time, the solution of this embodiment, by adding the oxide layer 3 and using the oxide layer 3 as a medium, transfers the test pattern from the photoresist through the oxide layer 3 to the metal layer 5, and finally forms an ohmic contact test structure.

[0076] Further, after the ohmic contact test structure is performed using the preparation method of the above steps S1 to S7, the electrical performance of the ohmic contact test of the same batch prepared is also tested, and the abnormality of the process parameters or equipment in the preparation method is queried based on the electrical performance to ensure the pass rate of the ohmic contact test structure. Specifically, the steps include the following steps:

[0077] First, the electrical performance of the ohmic contact test structures of the same batch is tested. Specifically, the electrical performance is resistance, that is, the resistance value corresponding to each ohmic contact test structure at different temperatures is obtained.

[0078] Secondly, based on the electrical properties of the ohmic contact test structures of the same batch, density clustering is performed on the ohmic contact test structures of the same batch to achieve binary classification and identify abnormal ohmic contact test structures.

[0079] In this embodiment, the cluster difference distance is obtained; and the ohmic contact test structures of the same batch are classified into two categories based on the cluster distance, so that the smaller category of the two categories is selected as the abnormal category.

[0080] The density clustering adopts the DBSCAN clustering algorithm. In this embodiment, there are two categories of binary classification, wherein the eps (search radius) in DBSCAN is adjusted to achieve binary classification, and the search radius can be adjusted by the implementer according to the specific real-time scenario.

[0081] The cluster difference distance in the above for:

[0082]

[0083] in, Test structure for ohmic contact X The resistance value sequence of the resistance value at different temperatures, Test structure for ohmic contact YThe series of resistance values ​​at different temperatures, Similarity () function is used to calculate the similarity function.

[0084] After clustering is completed, you also need to check the number of clusters generated. If the number of clusters is greater than 2, you can consider adjusting the values ​​of Eps and MinPts so that the number of clusters generated by DBSCAN is 2.

[0085] At the same time, since the DBSCAN clustering algorithm will mark some sample points that cannot be classified into any cluster as noise, the noise data will be classified into the clustering result with the minimum similarity, that is, into the abnormal category.

[0086] Finally, the current process parameters of each ohmic contact test structure in the abnormal category are obtained, and the consistency between the current process parameters and the normal process parameters is calculated. If the consistency is greater than the set threshold, the abnormal process parameters may be normal, and the staff is reminded to repair the equipment; otherwise, the staff needs to adjust the process parameters to re-prepare the ohmic contact test structure.

[0087] The consistency in the above steps is to evaluate the current process parameters by comparing the difference between each process parameter and the normal process parameter, and taking the ratio of the number of differences less than the set value to the total number of process parameters as the consistency. The process parameters include various combinations of size parameters, material parameters, process temperature, process time, etching amount and process pressure.

[0088] It should be noted that in this embodiment, it is assumed that the material parameters of the ohmic contact test structures prepared in the same batch are consistent, that is, the influence of the material parameters is ignored.

[0089] The normal process parameters mentioned above may be obtained through statistics of historical experience data, or may be parameters corresponding to a selected normal ohmic contact test structure.

[0090] Exemplarily, the process parameters in this embodiment include process temperature, process time, etching amount and process pressure, wherein the process temperature includes diffusion temperature, oxidation temperature and annealing temperature; the process time includes oxidation time and annealing time; the process pressure includes film deposition pressure and etching pressure. Therefore, the total number of process parameters mentioned above is 7. Then the setting of the above set values ​​can be set according to the resolution of the specific parameters. For example, when it is temperature, the set value can be 2°C; when it is annealing time, its set value can be 5 minutes. Of course, the specific set value needs to be determined according to the materials used, the size and requirements of the device, the annealing temperature and the target performance.

[0091] The threshold value set in the above may be 0.9, and its purpose is to evaluate whether the current process parameters are normal. That is, when the difference is less than the set value, the current process parameters are considered to be basically consistent with the normal parameters, and the current process parameters are considered to be normal. At this time, it is considered that there may be problems with the equipment used in the preparation, and the staff needs to repair the equipment. Otherwise, it is considered that there is a problem with the process parameters, and the process parameters need to be adjusted, and the ohmic contact test structure needs to be re-prepared to improve the pass rate.

[0092] In the above scheme, the electrical performance test of the ohmic contact test structure is tested to verify the pass rate of the prepared ohmic contact test structure, that is, starting from the process parameters and equipment, the abnormalities in each link are determined, so that a qualified ohmic contact test structure can be prepared; therefore, the scheme of the present invention, when preparing the ohmic contact test structure, is improved not only in terms of the process steps, but also verified from the prepared ohmic contact test structure to adjust the process parameters or equipment so that it can prepare a qualified ohmic contact test structure.

[0093] In the description of this specification, “plurality” means at least two, such as two, three or more, etc., unless otherwise clearly and specifically defined.

[0094] Although this specification has shown and described a number of embodiments of the present invention, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Those skilled in the art will conceive of many modifications, changes and alternatives without departing from the ideas and spirit of the present invention. It should be understood that in the practice of the present invention, various alternatives to the embodiments of the present invention described herein may be employed.

Claims

1. A method for preparing an ohmic contact test structure, characterized in that: The following steps are involved: providing a substrate layer; forming an oxide layer on the surface of the substrate layer; The material of the oxide layer is silicon dioxide, and the thickness of the oxide layer is greater than the thickness of the metal layer; Coating photoresist on the oxide layer, and obtaining a photoresist cover area and a non-photoresist cover area through exposure and development; Etching to remove the exposed oxide layer in the non-capping glue area; Removing the photoresist in the cover glue area to obtain a plurality of spaced oxide layers; forming a metal layer on the surfaces of the oxide layers and the exposed epitaxial layer; Wet etching is used to peel off several spaced oxide layers and metal layers on their surfaces to obtain an ohmic contact test structure; wherein the wet etching uses a BOE solution or an HF solution; and rapid annealing or laser annealing is performed before the wet etching; The method also includes testing the electrical properties of the ohmic contact tests of the same batch prepared, and querying the abnormalities of the process parameters or equipment in the preparation method according to the electrical properties to ensure the qualified rate of the ohmic contact test structure; The steps to ensure the pass rate of the ohmic contact test structure are: Testing the electrical properties of the ohmic contact test structures of the same batch; the electrical properties include resistance values ​​measured at different temperatures; Based on the electrical properties of the ohmic contact test structures of the same batch, density clustering is performed on the ohmic contact test structures of the same batch to achieve binary classification and determine the abnormal category; Obtain the current process parameters of each ohmic contact test structure in the abnormal category, calculate the consistency between the current process parameters and the normal process parameters, if the consistency is greater than the set threshold, the abnormal process parameters may be normal, then the staff is reminded to repair the equipment; otherwise, the staff needs to adjust the process parameters to re-prepare the ohmic contact test structure.

2. The method for preparing an ohmic contact test structure according to claim 1, characterized in that: The exposed oxide layer in the non-capping glue area is etched away by using a dry etching process; the parameters of the dry etching process include: etching gas, time, power and pressure.

3. The method for preparing an ohmic contact test structure according to claim 1, characterized in that: Before forming the oxide layer, the method further includes forming an epitaxial layer on the surface of the substrate layer.

4. The method for preparing an ohmic contact test structure according to claim 1, characterized in that: The density clustering adopts the DBSCAN clustering algorithm.

5. The method for preparing an ohmic contact test structure according to claim 4, characterized in that: The consistency is obtained by comparing the difference between each process parameter and the normal process parameter, and calculating the ratio of the number of differences less than the set value to the total number of process parameters.

Citation Information

Patent Citations

  • SiC Ohmic Contact Structure and its Fabrication Method

    CN107546112B

  • Method for stripping electrode

    CN101231948A

  • Photoluminescence-based solar crystalline silicon wafer quality prediction and control method

    CN103311374A